Investigation of yb3+ doped fiber laser - Xu, Shao Bin (2009)
Fiber lasers now compete directly in several domains with semiconductor lasers and solid-state lasers, over which they present the advantages of high brightness, excellent mode quality, high efficient coupling into a single mode fiber, and a far superior wavelength stability with temperature. Ytterbium-doped fiber lasers are amongst the most efficient of all rare-earth doped fiber lasers. A wide range of application for this versatile laser source can be anticipated.